K-span: Open and reproducible spatial analytics using scientific workflows - Forkan, Abdur; Both, Alan; Bellman, Chris; Duckham, Matt; Anderson, Hamish; Radosevic, Nenad (Frontiers in Earth Science, 2023)
This paper describes the design, development, and testing of a general purpose scientific workflows tool for spatial analytics. Spatial analytics processes are frequently complex, both conceptually and computationally. Sharing, adaptation, and reuse of bespoke spatial analytics procedures represents a growing challenge today, particularly in this era of big spatial data. Scientific workflow systems hold the promise of much greater reproducibility, scalability, and transparency in spatial analytics processes. Our tool (“K-span”) is implemented as an extension to the general-purpose open-source KNIME scientific workflow platform, by integrating a range of existing open-source spatial software and libraries. We used as a case study the modeling and construction of part of the Australian national DEM (Digital Elevation Model) by Geoscience Australia (GA). The outcomes of translating an established, documented analytics process into a scientific workflows highlight the benefits of using our system and our general approach. Most importantly in our case study, these benefits include the idea of warrantability, increasing the understanding of the provenance of foundational spatial data sets across diverse uses and user groups.